If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -1d + 6 Reorder the terms: 16 = 6 + -1d Solving 16 = 6 + -1d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add 'd' to each side of the equation. 16 + d = 6 + -1d + d Combine like terms: -1d + d = 0 16 + d = 6 + 0 16 + d = 6 Add '-16' to each side of the equation. 16 + -16 + d = 6 + -16 Combine like terms: 16 + -16 = 0 0 + d = 6 + -16 d = 6 + -16 Combine like terms: 6 + -16 = -10 d = -10 Simplifying d = -10
| 2b=-34 | | 10+3(x-13)=5(1-x)+14 | | -6x+2=-9+5x | | 4m+=13-m | | 7n-6+n=2(4n+3) | | (6a+11)=2a+83 | | x^2+121=2x^2 | | 7d-3d+5d-5-6d=0 | | b-2+3b+64=4 | | -136=8(1+6b) | | 16=2(x-1)-4 | | 4(3x+5)=104 | | 7.50=0.8c+0.5c | | 11=-7p+13+8p | | 6x-50=10-x | | 2m+23=7m-2 | | 0.5c-7.50= | | x^2-3x+24=0 | | 17x^2-22x+6=0 | | -4x+-40-6=-3-6 | | 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 | | b-2+3b+6=4 | | 6p-1=p+20 | | 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 | | -6+3X-3Y=0 | | 0=-Y+X-4 | | -3+2X=Y | | 7x+5x+10= |